Use of polyaniline coating on magnetic MoO3 and its effects on material stability and visible-light photocatalysis of tetracycline. Issue 3 (June 2022) - Fanourakis, Sofia K.; Barroga, Sharona Q.; Mathew, Riya A.; Peña-Bahamonde, Janire; Louie, Stacey M.; Perez, Jem Valerie D.; Rodrigues, Debora F.
Abstract: A semiconducting material (polyaniline-coated magnetic MoO3 ) with photodegradative properties and low solubility was synthesized and assessed in the degradation of tetracycline (TC) to address the rising concern of antibiotics in water systems. Polyaniline (PANI) provided a protective coating, significantly reducing MoO3 dissolution across a wide pH range, while the Fe3 O4 core facilitated photocatalyst extraction from water. Uncoated MoO3 @Fe3 O4 dissolution significantly increased with increasing pH (dissolved Mo percentage of 2.9% at pH 3 and 22.9% at pH 10). With the PANI coating, dissolution was reduced to 1.6% at pH 3 and 5.6% at pH 10. The TC removal by PANI@MoO3 @Fe3 O4 was 8.2 mg TC/g photocatalyst in visible light and 6.5 mg/g in dark within 35 min under optimum conditions. The degradative properties of PANI@MoO3 @Fe3 O4 toward TC were facilitated by reactive species produced from water oxidation by photogenerated holes ( h + ). This initial assessment of PANI@MoO3 @Fe3 O4 as a photocatalyst for pharmaceutical contaminant degradation indicates PANI@MoO3 @Fe3 O4 is a promising material useful for wider environmental applications. Graphical Abstract: ga1 Highlights: The high solubility of MoO3 makes it inefficient for water treatment. Coating magnetic MoO3 @Fe3 O4 with polyaniline (PANI) reduces its dissolution. MoO3 @Fe3 O4 coating with PANI increases photocatalytic activity by 20%. PANI@MoO3 @Fe3 O4 degrades tetracycline by producing reactive oxygen species. Mobile active sites of PANI promoted the oxidation of water by photogenerated h + .